The Effects of Exercise on Inhibitory Function Interventions for Patients With Major Depressive Disorder (MDD): A Systematic Review and Meta‐Analysis - Zhihui Xu; Cong Liu; Peng Wang; Xing Wang; Yuzhang Li (Brain and Behavior)
ABSTRACT Background Systematic Review of The effects of exercise on inhibitory function interventions for patients with major depressive disorder. Methods We searched PubMed, Web of Science, EMbase, The Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang Database, and China Science and Technology Journal Database (CQVIP) for randomized controlled trials (RCTs) investigating the impact of exercise on inhibitory function in MDD patients, from database inception to July 2024. Two researchers independently evaluated the quality of the included studies using the Risk of Bias (ROB 2.0) tool. Evidence quality was assessed with the GRADE profiler software, and effect sizes were combined using Stata 17.0 software to create forest plots, test for publication bias, and perform sensitivity analyses. Results A total of nine RCTs involving 1038 participants from six countries, published between 2001 and 2022, were included. The average age of participants in both the experimental and control groups was 45 years. Meta‐analysis results indicated that exercise significantly improves inhibitory function in MDD patients, with a combined effect size (SMD = 0.48, 95% CI = 0.18–0.77, p < 0.001). Subgroup analysis showed that exercise had a statistically significant effect on inhibitory control in MDD patients, with an effect size (SMD = 0.563, p < 0.001). Regarding exercise elements, other types of exercise (resistance exercise RE, mixed exercise ME), duration greater than 45 min, intervention period of ≤12 weeks, frequency of two times per week, and low intensity were found to be more effective, all with statistical significance (SMD = 0.863, p < 0.001; SMD = 0.936, p < 0.001; SMD = 0.525, p = 0.002; SMD = 0.682, p = 0.004; SMD = 0.94, p = 0.00). Conclusion Based on the International Classification of Diseases (ICD) and the Diagnostic and Statistical Manual of Mental Disorders (DSM) classification systems, a research framework for exercise interventions on executive function in MDD patients was constructed, demonstrating that exercise can improve inhibitory function in MDD with high evidence quality. Our study found that other types of exercise (RE or ME), intervention duration of >45 min, intervention period of ≤12 weeks, frequency of two times per week, and low intensity are more effective for improving inhibitory function in MDD patients. While the overall methodological quality of the literature was good, high heterogeneity existed among studies. Subgroup analysis suggested that sources of heterogeneity included measurement tools, exercise types, exercise intensity, duration, and frequency. Sensitivity analysis indicated that exercise duration and period might be causes of heterogeneity. This study has some limitations as the included literature did not consider disease duration, depression severity, or categorize age groups. However, the findings provide strong evidence for clinical practice and future research on the beneficial effects of exercise on inhibitory function in MDD patients. Trial Registration CRD42023480371